Frecuencia de parásitos intestinales en equinos de trabajo provenientes de los municipios: Caracolí y San Roque del departamento de Antioquia, Colombia - Julio-Olave, E.; Londoño-Isaza, V.; Eraso-Cadena, M.; Llano, H. A. B. (Revista Veterinaria, 2025)
Colombia has a horse culture, but there are few reports on the frequency or prevalence of gastrointestinal parasitism in working horses (those used for traction). Therefore, this study aimed to determine the frequency of gastrointestinal parasites in fecal samples from horses in two areas of the Antioquia department, Colombia, specifically the municipalities of Caracolí and San Roque. Between March and August 2022, researchers collected fecal samples directly from the rectum of 44 Colombian Criollo horses and examined them using sedimentation and flotation methods. An overall frequency of 77.3% (34/44) was recorded, with genera such as Strongylus spp. (91.2%), followed by Oxyuris equi (15.9%), Parascaris spp. (5.9%), and Anoplocephala spp. (2.9%). Among the positive samples, 79.4% showed monoparasitic infections, while the remaining 20.6% had biparasitic associations. We found no statistically significant differences between the positive animals and the variables of origin, sex, age, or body condition. The results highlight the high frequency of nematodes, mainly Strongylus spp., in working horses from these two municipalities in Antioquia. The existence of these helminths highlights the necessity of establishing deworming initiatives to reduce their effects on the health and productivity of these animals.